(untitled) (Journal of Scientific Research, 2009)
Leaves of Actinodaphne hookeri (AH) Meissn (family, lauraceae, pisa) are used traditionally in the treatment of diabetes, disorders of the urinary tract which are more common in Chhattisgarh and eastern part of India. It contains flavonoids and quercetin-3-rhamnoside as an important constituent. The leaves were extracted with 70% hydro alcoholic solvent. Preliminary phytochemical investigation showed the presence of triterpenoids, alkaloids, tannins, flavonoids, glycosides and carbohydrates. The antioxidant activity of 70% hydro alcoholic extracts of AH was evaluated in vitro by various experimental parameters such as b-carotene-linoleic acid, lipid peroxidation and total antioxidant capacity. Our results showed that Actinodaphne hookeri leaves displayed potent antioxidant properties, supporting the ethnomedical use given to this plant to treat diabetes and urinary disorder. Keywords: Actinodaphne hookeri; Antioxidant; Lipid peroxidation; Total antioxidant capacity. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2266 J. Sci. Res. 1 (3), 606-614 (2009)